การศึกษาพฤติกรรมความเป็นผู้นำในงานวิชาการของผู้บริหารสถานศึกษา ระดับมัธยมศึกษา สังกัดกรมสามัญศึกษา จังหวัดอุดรธานี - ประภาพันธ์ เจริญกิตติ (จุฬาลงกรณ์มหาวิทยาลัย, 2000)
The purpose of this research was to study the leadership behavior in academic task of secondary school administrators under the general education department, udon thani province. Sample were 53 administrators and 335 teachers. Data were analyzed by the Statistic Package for the Social Science and presented in items of frequency, percentage, mean, standard deviations. The findings were as follows : According to the opinions of the administrators and teachers, concerning about the leadership behavior in academic task of secondary school administrators in 7 aspect, were rated at high level. They were ranked as follows : 1 ) the school administrator as a recognizer in academic task ะ 2) the school administrator as a helper in academic task ; 3) the school administrator as an initiator in academic task ; 4) the school administrator as an improver of academic task ; 5) the school administrator as an effective speaker in academic task ; 6) the school administrator as a co-ordinator in academic task and ; 7) the school administrator as a social man for the benefit of academic task